GLUTELIN PRECURSOR ACCUMULATION3 Encodes a Regulator of Post-Golgi Vesicular Traffic Essential for Vacuolar Protein Sorting in Rice Endosperm . Issue 1 (31st January 2014) - Ren, Yulong; Wang, Yihua; Liu, Feng; Zhou, Kunneng; Ding, Yu; Zhou, Feng; Wang, Ying; Liu, Kai; Gan, Lu; Ma, Weiwei; Han, Xiaohua; Zhang, Xin; et al.
Abstract : Dense vesicles (DVs) are known to be key carriers for sorting of storage proteins to protein storage vacuoles (PSVs) in seed plants. This work characterizes the kelch-repeat protein GLUTELIN PRECURSOR ACCUMULATION3, which forms a functional protein complex with the small GTPase Rab5a via its guanine exchange factor, VPS9a, to regulate directional trafficking of DVs to PSVs in rice endosperm. Abstract: In seed plants, a major pathway for sorting of storage proteins to the protein storage vacuole (PSV ) depends on the Golgi-derived dense vesicles (DVs ). However, the molecular mechanisms regulating the directional trafficking of DVs to PSVs remain largely elusive. Here, we report the functional characterization of the rice ( Oryza sativa ) glutelin precursor accumulation3 ( gpa3 ) mutant, which exhibits a floury endosperm phenotype and accumulates excess proglutelins in dry seeds. Cytological and immunocytochemistry studies revealed that in the gpa3 mutant, numerous proglutelin-containing DVs are misrouted to the plasma membrane and, via membrane fusion, release their contents into the apoplast to form a new structure named the paramural body. Positional cloning of GPA3 revealed that it encodes a plant-specific kelch-repeat protein that is localized to the trans -Golgi networks, DVs, and PSVs in the developing endosperm. In vitro and in vivo experiments verified that GPA3 directly interacts with the rice Rab5a-guanine exchange factor VPS9a and forms a regulatory complex with Rab5a via VPS9a. Furthermore, our genetic data support the notion that GPA3 acts synergistically with Rab5a and VPS9a to regulate DV -mediated post-Golgi traffic in rice. Our findings provide insights into the molecular mechanisms regulating the plant-specific PSV pathway and expand our knowledge of vesicular trafficking in eukaryotes.